The southernmost South American record of the genus Halicyclops Norman, 1903 (Cyclopoida: Cyclopidae) with the description of a new species - Menu-Marque, Silvina; Sorarrain, Dora (Zootaxa, 2007)
Species of the cyclopid genus Halicyclops are widespread in coastal, estuarine and even fluvial environments worldwide. On the Atlantic coast of South America several species have been recorded as far south as the state of São Paulo in Brazil, at about 24°25´S. Specimens belonging to this genus have been collected from plankton samples from Laguna de Mar Chiquita, a coastal lagoon on the Argentinean coast at 37°40' S, 57°19' W. These do not fit the diagnosis of any of the known species, and are here described as a new species. Both sexes of Halicyclops ramirezi sp. nov. are described and illustrated. It is distinguished by a combination of characters relating to (1) the last endopodal segment of P4, (2) shape and armature of P5, (3) size and spinulation of the spine on the basipodite of P1, and (4) length/width ratio of the fourth A1 segment. The presence of only one seta and three spines on the male P5 is also characteristic. The presence of Halicyclops glaber Rocha, 1983 is reported for the first time for Argentina in sediments of the same locality.